Konsep Keabadian dan Waktu dalam Perspektif Pemikiran Islam - Oktarika, Dina (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2023)
Intellectual pluralism which refers to a variety of views and approaches in understanding Islamic teachings, which allows different interpretations of certain aspects of Islamic beliefs and philosophy which focuses on the concepts of "time" and "eternity" which over time have decreased in the Islamic philosophical tradition includes interpretations of philosophers and theologians from various schools of Islamic thought by identifying differences and similarities in the views of figures such as al- Kindi, al- Farabi, Ibn Sina (Avicenna), and al- Ghazali, who represent interpretations in understanding the relationship between time and eternity in the context of Islamic metaphysics. Pluralism as part of the tradition of Islamic thought links between Islamic metaphysical concepts in a wider cultural, social and historical context. The concepts of "time and eternity" in the understanding of the relationship between finite universes refer to the time dimension of temporality and eternity which posits the existence of matter and divine reality. Time is an aspect related to changes and events in a finite universe, the universe has a beginning and an end in a sense. Time is also related to dimensions where a dimension is not complete if there is no time. The concept of eternity refers to a divine dimension or eternity that exists beyond the finite time frame of the universe. In Islamic thought, God is considered as an eternal entity that is not limited by time. This concept reflects the eternal and infinite nature of God in the Islamic theological tradition. Relationships between dimensions can create a finite temporal dimension of the universe and an eternal dimension of eternity. In this view, the universe is in a time frame while God as the creator of the universe exists outside the time dimension. This relationship can be interpreted as the relationship between the finite and the infinite, between the temporary and the eternal. Through this relationship it provides a basis for explaining how material reality and divine existence interact in different ways. This raises questions about the origin and the purpose of the universe as well as the role of humans in this scheme of relations. Overall, the concept of "time and eternity in the understanding of the relationship between finite universes reflects an attempt to cover up the complexity of the relationship between time, temporality and eternity in the context of Islamic thought. Interpretation and understanding of these concepts can vary, and philosophical and theological thinking plays a role in develop a deeper understanding of the relationship with the universe.